ANALISIS USAHATANI TEBU DI LAHAN TEGALAN KASUS DI KABUPATEN BONDOWOSO - Mulyono, Daru (Badan Pengkajian dan Penerapan Teknologi, 2006)
The objectives of the research are to know the description of sugarcane enterprise especially concerning with coat and income, to know the sugarcane practice as a guide to farmers within their enterprise, and to increase input guarantee of raw material to sugarcane factory. The research was carriedout through gathering primary data by using questionaire with farmers as respondents. The respondents were selected by method of Stratified Purposive Random Sampling. The field survey was done in Bondowoso Regency, from 24th August untill 7th September 2004. The data was analyzed by using: hypothesis testing, break even point analysis, and sensitivity analysis. The results of the research show that the average of net farmers income from new planted sugarcane reach to a high of Rp. 4,507,584,-/year whereas from ratoon sugarcane reach to a high of Rp 3,272,307,-/year. The recommendation for sugarcane self sufficiency is by using productive arid land especially in Java with optimally agricultural inputs and cultivate according to standard operational procedure.